How do interconnected dynamics of climate, security and human mobility interplay in Guatemala? Climate security and human mobility pathway analysis - Higuera-Florez, Julian; Madurga Lopez, Ignacio M.; Penel, Charlotte; Carneiro, Bia; Pacillo, Grazia; Läderach, Peter R.D. (2023)
Guatemala is characterized by high rates of poverty and inequality, as well as a significant incidence of violent acts and generalized social tension. Climate change impacts on temperatures, rainfall patterns and extreme weather events are deepening the challenges of marginalized populations regarding food security, livelihood options, housing needs and access/availability of natural resources. Domestic and international migration constitutes a common adaptative strategy for individuals, households and communities experiencing these hardships, while also posing a challenge to populations suffering from involuntary immobility. However, human mobility can also trigger conflicts, social tensions and human security risks. Simultaneously, violence, socioenvironmental conflicts, and extreme weather and geophysical events are common drivers of displacement. In turn, displacement is also frequently linked to socioeconomic and climate vulnerabilities, as well as social tensions and human security risks. However, human mobility does not necessarily always lead to conflict or insecurity, as there are also cooperative opportunities in addressing climate change to foster resilience and peace. Consequently, it is important to understand how these interconnections and compounding risks interplay across Guatemala and how it operates differently across geographic, economic, gender and social dimensions. The purpose of this factsheet is therefore to explore these complex interactions between climate, security and human mobility in Guatemala. To acknowledge and conceptualize these interactions four main pathways were identified: